Bangla derivational suffix: An approach to reanalysis - Asaduzzaman, Muhammad (Dhaka University Journal of Linguistics, 2009)
Bangla derivational suffix is very potential to form a word. In Bengali traditionally such linguistic category is analyzed with the help of meaning and structure of a word together. But nowadays this idea has been changed, and it is being justified on the basis of either of the component mentioned above. This article clarifies the usages of the Bangla derivational suffix and its structure. Dhaka University Journal of Linguistics Vol.1(1) 2008